Metropolen-orientierte Politik und territoriale Kohäsion — Notwendigkeit oder Widerspruch? - Küpper, Patrick (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
Regularly, new concepts on how the territory should develop arise in spatial planning politics. Previous ideas include: active or passive restructuring, functionally balanced territories or interregional specialization, target for balance or growth. Current discussions are concerned with European metropolitan regions and territorial cohesion. This contribution seeks a theoretical foundation of the metropolitan-oriented policy. Three main implications for territorial cohesion are derived from these theories and concepts. The possibilities of compensation payments, spill over effects and interregional specialization are identified and critically analysed. Thus, the article demonstrates the lack of clarity in theory and the conflicts between the objective and the concept.